Antioxidant activity of panJe tea combination of pandan (Pandanus amaryllifolius) and jahe (Zingiber officinale) - Wahyu Widowati; Teresa Liliana Wargasetia; Teddy Marcus Zakaria; Michael Sebastian Gunadi; Sherly Santiadi; Meganita Marthania; Abdullah Rasyad Ziyad (Universitas Ahmad Dahlan, 2023)
Herbal tea are popular because of their potential herbal medicine, a blend of herbal ingredients, promised to provide a specific purpose. The main purpose is to determine antioxidant activity in herbal teas (pandan mixed ginger) and in their infusions, as well as to obtain more complex information about the tea products. In this study, DPPH radical scavenging, H2O2 scavenging, ABTS reduction, and FRAP reduction assay were carried out. These assays are proved that the IC50 values of ginger are higher than PanJe and pandan. For DPPH scavenging, H2O2 scavenging, FRAP scavenging, ABTS reduction activities, PanJe resulted IC50 14.69 ¼g/mL, 27.70 ¼g/mL, 7.09 ¼g/mL, and 411.28 µg/mL, while ginger yielded IC50 7.76 ¼g/mL, 13.23 Î¼g/mL, 4.94 ¼g/mL ,and 125.95 respectively. Otherwise, the highest total phenolic and flavonoid of panje were shown at 1.60 ± 0.26 µg QE / 100% extract and 8.67 ± 0.80 µg QE/100% extract respectively. Based on these results, PanJe, pandan and ginger are concluded as an active natural product because it exhibited antioxidant activities from two mixed compounds.